Procalcitonin and nSOFA at Sepsis Evaluation: Diagnostic Accuracy for Late-Onset Sepsis and 7-Day Mortality in Preterm Neonates: A Cross-Sectional Analytic Study - Morsi, Walaa E.M.A.; S, ElAnwary; Tadros , Mourad Alfy; Sanad, Hesham Abdellatif; Hassan , Nora; Metwalli, Eman Mahmoud (Adolescência e Saúde, 2026)
Background: Late-onset sepsis (LOS) in preterm neonates is difficult to confirm at clinical deterioration, yet early risk stratification is crucial. This study evaluated the diagnostic accuracy of procalcitonin (PCT) and neonatal Sequential Organ Failure Assessment (nSOFA) score for culture-confirmed LOS and 7-day mortality. Methods: This cross-sectional analytic study included 200 preterm neonates (<34 weeks’ gestation, >72 hours of age) evaluated for suspected LOS in the NICUs of Cairo University Children’s Hospital. Clinical and laboratory assessment included gestational age (GA), anthropometry, complete blood count, CRP, PCT, blood culture, and nSOFA score. Culture-confirmed LOS was defined by positive blood culture. Results: Mean GA was 30.77±2.15 weeks, mean PCT 6.25±9.93 ng/mL, and mean nSOFA 5.5±3.27. Neonates who died had lower GA (29.14 vs 31.15 weeks, P<0.001), higher PCT (12.83 vs 4.71, P<0.001), and higher nSOFA (8.47 vs 4.80, P<0.001). Neonates with sepsis had lower GA (30.26 vs 31.14 weeks, P=0.003), higher PCT (8.26 vs 4.79, P<0.001), and higher nSOFA (6.43 vs 4.82, P=0.001). For sepsis prediction, PCT had the highest AUC (0.69), followed by nSOFA (0.64) and CRP (0.57). For mortality, nSOFA showed the highest AUC (0.82), followed by GA (0.78) and PCT (0.77). lnPCT independently predicted sepsis (OR 1.56, P=0.003), while lower GA, higher nSOFA, and higher lnPCT independently predicted mortality. Conclusions: At sepsis evaluation in preterm neonates, PCT was the strongest individual predictor of culture-confirmed LOS, whereas nSOFA was the best predictor of 7-day mortality. Combined assessment of inflammatory response and organ dysfunction may improve early bedside stratification in suspected LOS.